Enhancing Problem-Solving Abilities of Teachers and Students through Integrated Computational Thinking Training in the Curriculum - Jaya, Safitri (STMIK Widya Cipta Dharma, 2025)
Computational Thinking (CT) is a problem-solving approach that utilizes fundamental concepts of computer science. CT involves systematic and logical thinking to break down complex problems into smaller, manageable parts, recognize patterns, perform abstractions, and design algorithmic solutions. This skill is crucial in 21st-century learning as it helps teachers and students develop better problem-solving abilities. A relevant 21st-century curriculum should include skills such as computational thinking, problem-solving, collaboration, and communication. This training aimed to identify teachers' and students' abilities in solving problems using their existing knowledge and skills. The training was conducted using a blended learning method, featuring lectures, exercises, and quizzes. The activity took place at Erenos School in South Tangerang, involving 52 teachers and 184 students from elementary to high school levels. The training, organized by the Bebras Bureau of Universitas Pembangunan Jaya (UPJ), showed an improvement in analysis, synthesis, and evaluation skills among teachers and students who participated in the CT training integrated with the curriculum. The evaluation results revealed a significant increase in students' and teachers' understanding and application of CT concepts in real-life scenarios. Furthermore, teachers reported increased confidence in developing CT-based lesson plans and incorporating computational principles into everyday learning. These findings support the importance of CT integration into the national curriculum to enhance educational quality and equip learners with essential skills for the digital era.